Cost-Utility of an Objective Biochemical Measure to Improve Adherence to Antihypertensive Treatment. Issue 5 (November 2018) - van Schoonhoven, Alexander V.; van Asselt, Antoinette D.I.; Tomaszewski, Maciej; Patel, Prashanth; Khunti, Kamlesh; Gupta, Pankaj; Postma, Maarten J.
Abstract : Nonadherence to antihypertensive medications is known to be a major health problem. Novel biochemical analyses using liquid chromatography-tandem mass spectrometry are becoming accepted as a clinically useful objective measure to manage (non)adherence in Hypertension Clinics. Discussion of results from such analyses with patients can significantly improve adherence and blood pressure control. Our objective was to model the cost-effectiveness of performing liquid chromatography-tandem mass spectrometry-based analyses in improving adherence in patients with hypertension. Lifetime cost-utility was assessed from a UK healthcare payer perspective, using a Markov model. Efficacy was based on study findings of lowering blood pressure because of improved adherence to drug treatment. Cost and utilities were derived from literature. The base case cohort consisted of males aged 65 years. Subgroup analyses included varying population sex and age and a subgroup of patients with apparent resistant hypertension. Additionally, univariate and probabilistic sensitivity analyses were performed. Our findings are reported after the Consolidated Health Economic Evaluation Reporting Standards checklist. Per patient, screening resulted in 0.020 incremental quality-adjusted life-years and a negative incremental cost of £495, suggesting the intervention to be dominant compared with care as usual. Targeting younger patients or patients with apparent resistant hypertension would further improve these outcomes. Modeling suggested that screening prevented 518 myocardial infarctions and 305 stroke events in a cohort of 10 000 male hypertensive patients. Using liquid chromatography-tandem mass spectrometry-based biochemical analyses to improve adherence in hypertensive patients is likely to be an effective and cost-saving strategy, especially in patients with apparent resistant hypertension. Abstract : Supplemental Digital Content is available in the text.